Case report: Immune checkpoint inhibitor-induced fulminant diabetic ketoacidosis: a case-based review and considerations for immunotherapy discontinuation - Zhao, Shanshan; Liu, Xin; Tan, Pengcheng; Mu, Yuejun; Tan, Song; Hou, Aihua (Frontiers in Immunology, 2026)
ObjectiveTo report a case of advanced lung adenocarcinoma (LUAD) harboring KRAS p.G12C and TP53 p.R273C mutations. While immune checkpoint inhibitor (ICI) therapy offered remarkable clinical benefits, it concurrently induced a fatal endocrine complication, highlighting the dual-natured impact of immunotherapy.Case presentationAn elderly male diagnosed with Stage IV LUAD achieved sustained stable disease (SD) and symptomatic improvement through a sequential therapeutic strategy, including platinum-based chemotherapy followed by the PD-1 inhibitor sintilimab combined with anti-angiogenic agents (apatinib or anlotinib). However, the patient developed severe coma, hyperglycemia and metabolic disorder. Laboratory investigations confirmed fulminant ICI-related diabetic ketoacidosis (DKA). Despite intensive resuscitative efforts, the patient succumbed to multi-organ failure.Discussion and conclusionsThis case demonstrates that while ICIs can provide exceptional long-term benefits in advanced NSCLC, particularly in patients with highly immunogenic mutation profiles, they may also trigger late-onset fatal irAEs. Our findings underscore the imperative for close, long-term metabolic surveillance throughout the course of immunotherapy, regardless of treatment duration or radiological stability.